Study of Hypercoagulability in Patients with Acute Leukaemia in the Hematology Department of Teaching Hospital of Yopougon (Abidjan) - Mahawa, Sangaré-Bamba; Valère, Tchako; Hermance, Kassi-Kablan; Rebecca, N’Guessan-Blao; N’Dogomo, Meité; Mireille, Yayo-Ayé; Duni, Sawadogo (Journal of Hematology and Oncology Research, 2020)
Introduction Acute leukaemia are the clonal and malignant proliferation of immature hematopoietic cells (blast), blocked in their differentiation process. There is an interaction between cancer cells and the clotting process. This could be the expression of Tissue Factor (TF) on the surface of tumor cells; or a lesion of the vascular endothelium and platelet activation. The result is an activation of clotting that can lead to disseminated Intravascular Coagulation (DIC). The objective of this study was to assess the risk of DIC occurring in patients with acute leukaemia. Methods This was a cross-sectional study for analytical purposes that took place on 40 frozen samples from the biobank of the haematology laboratory of Teaching Hospital Yopougon for which the diagnosis of acute leukaemia had been taken from myelogram. The myelogram results were accompanied by hemogram data. PTTa, QT, fibrinogen and D-Dimers were performed on these samples. The risk assessment of DIC occurred was determined on the recommendations of the International Society of Thrombosis and Hemostasis (ISTH). Results We noted a female predominance with a Sex Ratio (M / F) of 0.90. The average age of the patients was 38 years (± 23 years) with extremes ranging from 2 to 84 years. ALL represented 20 % of cases against 80 % for AMLs. Hemogram parameters were characterized by severe anaemia (Tx Hb < 6 g / dL) in 52.5 % of cases; hyperleukocytosis > 100.103 / mm3 in 35 % of cases; thrombocytopenia < 25.103 / mm3 in 40 % of case; and significant blood and spinal cord blastosis (> 80 %). The lengthening of the PTTa was observed in 50 % of cases, compared to 40% for the QT. Similarly, hyperfibrinemia was present in 65% of cases. D-Dimers were high in almost all subject (95 % of cases). According to the ISTH criteria, 17.5 % of subjects were at risk of developing a DIC. Conclusion The risk of occurrence of DIC is indeed present during acute leukaemia. The parameters of haemostasis are thus found to be crucial data in the follow-up assessment during the diagnosis of acute leukaemia.
Keywords: Acute leukaemia; haemostasis; D-Dimers; Abidjan